Lead paste for negative electrode of lead-acid battery and preparation method thereof
By adding indium trioxide, vanillin, sodium polyaspartate and carboxymethylcellulose to the negative electrode formula of lead-acid battery, the serious problems of negative electrode sulfate and hydrogen evolution are solved, the battery life and low temperature performance are improved, and the large current discharge capacity is enhanced.
Patent Information
- Application Number
- CN202111611803.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-27
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2041-12-27
AI Technical Summary
The negative electrode of existing lead-acid batteries is prone to sulfate during use, resulting in a decrease in the porosity of the electrode plate, a decrease in conductivity, and a reduction in charge and discharge capacity. Acetylene black leads to severe hydrogen evolution and ends the battery life ahead of schedule.
By adding indium trioxide and vanillin to the formula to increase the hydrogen evolution overpotential of the negative electrode, inhibiting hydrogen precipitation; increasing sodium polyaspartate is used to control the crystallization process of lead sulfate, improving crystal form and crystal size; using carboxymethyl cellulose to prevent bubbles from being separated from the grid, and improving the performance of high-current discharge.
It improves battery life, prevents the attenuation of the low-temperature capacity of the negative electrode during circulation, and enhances the low-temperature performance and high-current discharge capability of the battery.
Smart Images

Figure CN114243000B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lead-acid batteries, in particular to a lead paste for negative electrodes of lead-acid batteries and a preparation method thereof. Background Art
[0002] With the increasing awareness of environmental protection and the increasing demand for clean and renewable energy, the application of lead-acid batteries in various industries has been transformed from small current and low power to large current and high power, which requires lead-acid batteries to have higher specific energy and longer service life. However, the negative electrode of existing lead-acid batteries is prone to sulfation during use, which reduces the plate porosity, conductivity, and charge and discharge capacity.
[0003] In the traditional negative electrode additive, acetylene black is used as a conductive material. For example, the invention application with publication number CN113394400A discloses a negative electrode lead paste, a negative electrode plate and a lead-acid battery of a lead-acid battery, which belongs to the technical field of lead-acid batteries. A negative electrode lead paste of a lead-acid battery comprises lead powder and an additive, wherein the additive comprises the following components: based on the total lead powder mass, 0.9-1wt% of barium sulfate, 0.3-0.4wt% of acetylene black, 0.05-0.08wt% of lignin, 0.5-0.8wt% of humic acid, 0.07-0.08wt% of short fibers, 0.03-0.05wt% of nano-silica sol and 0.55-0.7wt% of aminosulfonic acid.
[0004] For another example, the invention application with publication number CN104900876A discloses a new negative electrode active material for lead-acid batteries using graphene as an additive, which is composed of the following components by weight percentage: 0.5-1.2% colloidal graphite, 0.5-0.8% humic acid, 0.3-0.8% lignin, 0.5-1.2% barium sulfate, 0.07-0.2% short fibers, 0.05-0.15% polytetrafluoroethylene, 0.03-0.2% polyvinyl alcohol, 0.1-0.2% 1,2-propylene glycol, 0.1-0.3% graphene, 0.8-1.5% acetylene black, 75-85% lead powder, 7%-10% dilute sulfuric acid solution, and the rest is deionized water.
[0005] The following disadvantages may occur during actual use: 1. Acetylene black will cause serious hydrogen evolution at the end of battery charging, especially after the battery has been charged at 100% DOD for more than 200 times, the water damage is serious, resulting in the premature end of the battery life; 2. Polytetrafluoroethylene is an insulator. Adding it to the formula can bond the active substances, but it will increase the internal resistance of the battery and reduce the low-temperature performance of the battery; 3. The use of lignin and humic acid can improve the low-temperature performance of the battery, but the low-temperature capacity decays seriously during the cycle. Summary of the invention
[0006] The invention aims at the deficiencies in the prior art and provides a lead paste for negative electrodes of a lead-acid battery and a preparation method thereof. Indium trioxide and vanillin are added to the formula to increase the hydrogen evolution overpotential of the negative electrode, inhibit hydrogen evolution, and improve the battery life. Sodium polyaspartate is added to the formula to control the crystallization process of lead sulfate, improve the crystal form and crystal size of the lead sulfate, improve the utilization rate of the negative electrode active material, reduce the internal resistance of the negative electrode plate, and prevent and slow down the attenuation of the low-temperature capacity of the negative electrode during the cycle. Carboxymethyl cellulose is added to the formula to prevent the negative plate from bubbling and separation from the grid and improve the large current discharge performance of the battery.
[0007] A lead paste for negative electrodes of lead-acid batteries, the formula of which includes lead powder, negative electrode additive, deionized water and synthetic paste acid, wherein the negative electrode additive includes the following components in parts by weight, based on 100 parts by weight of the lead powder:
[0008]
[0009] Preferably, based on 100 parts by weight of lead powder, the negative electrode additive includes the following components in parts by weight:
[0010]
[0011] Preferably, the addition ratio of humic acid, sodium polyaspartate and lignin is 2-3:1:1-1.5.
[0012] Preferably, the addition ratio of the graphene to acetylene black is 1:2-2.33.
[0013] Preferably, based on 100 parts by weight of the lead powder, the weight of the deionized water is 10.5 to 11 parts.
[0014] Preferably, based on 100 parts by weight of lead powder, the weight of the composite acid is 7.6 to 8 parts. The density of the composite acid is 1.4±0.001 g / cm 3 .
[0015] The preparation method of the lead-acid battery negative electrode lead paste comprises the following steps:
[0016] (1) Add lead powder, lignin, barium sulfate, humic acid, sodium polyaspartate, acetylene black, carboxymethyl cellulose and indium trioxide into a paste mixer and stir evenly;
[0017] (2) Take 2 parts of the formulated water, add the formulated amount of graphene, fiber, and vanillin, and stir until the vanillin is dissolved, the graphene and fiber are evenly dispersed in the water, and the fiber does not clump.
[0018] (3) adding deionized water into the paste mixer while stirring, and adding the suspension produced in step (2) while stirring evenly;
[0019] (3) Adding the paste acid into the paste mixing machine while stirring, controlling the paste temperature to a maximum of 40 to 55° C., and stirring evenly;
[0020] (4) When the lead paste temperature is lower than 45°C, it can be taken out of the pot and used for coating the board.
[0021] The negative electrode of the battery has very rich pores and a highly developed surface area. In this state, the negative electrode surface has a high surface energy and is an unstable state. As the number of battery cycles increases, the surface area of the active material will shrink, causing the battery capacity to decay and the battery's low-temperature performance to deteriorate.
[0022] The negative electrode lead paste additive sodium polyaspartate (PASP) of the present invention can be adsorbed on the surface of lead and lead sulfate with hydroxyl, carboxyl and methoxy groups in lignin and humic acid, and can inhibit the transformation of the lead sulfate layer into a selective semipermeable membrane, thereby playing a role in depassivation and preventing or slowing down sulfation. The main functional groups of polyaspartic acid are carboxyl, carbonyl, imino, amide, etc. Different functional groups have different expansion effects. The addition of polyaspartic acid can control the crystallization process of lead sulfate, improve the crystal form and crystal size of lead sulfate, improve the utilization rate of negative electrode active materials, reduce the internal resistance of the negative electrode plate, and prevent and slow down the attenuation of the low-temperature capacity of the negative electrode during the cycle.
[0023] Both graphene and acetylene black have conductive properties, which enable the negative electrode active material to quickly form a highly conductive network during the formation process, thereby improving the formation efficiency. During the mixing process of lead paste, graphene and acetylene black are affected by particle size and lead affinity. Graphene is mainly concentrated on the branches of the active material skeleton and on the surface of the active material, which improves the charging acceptance of the active material. Acetylene black is a skeleton component of the active material and can also act as a supercapacitor. However, in the later stage of charging, due to the high voltage of the battery, graphene and acetylene black will seriously precipitate hydrogen, especially after the battery has been deeply cycled for more than 200 times, which will lead to serious water loss and premature termination of the battery life. For this reason, indium trioxide and vanillin are added to the formula to increase the negative electrode hydrogen evolution overpotential, inhibit hydrogen precipitation, and improve battery life. Carboxymethyl cellulose plays a bonding role in the active material, preventing the active material from bubbling and detaching from the grid. Because of its excellent water absorption characteristics, it makes the electrolyte more soluble and easy to penetrate into the active material, increasing the utilization rate of the active material and the high current discharge performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a comparison chart of the 2Hr capacity of a 20AH battery made of Examples 1 to 3 and Comparative Examples 1 to 3 and a 20AH battery made of a conventional electric vehicle negative electrode lead paste formula produced by the company, tested according to GB / T22199.1-2017.
[0025] Figure 2 This is a comparison chart of -18°C low-temperature capacity of 20AH batteries made of Examples 1 to 3 and Comparative Examples 1 to 3 and pastes, and 20AH batteries made of conventional electric vehicle negative electrode lead paste formula produced by the company, tested according to GB / T22199.1-2017.
[0026] Figure 3 This is a comparison chart of the capacity retention rates of 20AH batteries made of Examples 1 to 3 and Comparative Examples 1 to 3 and pastes, and 20AH batteries made of conventional electric vehicle negative electrode lead paste formula produced by the company, tested according to GB / T22199.1-2017.
[0027] Figure 4 This is a comparison chart of battery cycle life of 20AH batteries made of Examples 1 to 3 and Comparative Examples 1 to 3 and 20AH batteries made of the paste and conventional electric vehicle negative electrode lead paste formula produced by the company tested according to GB / T22199.1-2017.
[0028] Figure 5 This is a comparison chart of -18°C low-temperature capacity of 20AH batteries made of Examples 1 to 3 and Comparative Examples 1 to 3 and pastes, and 20AH batteries made of conventional electric vehicle negative electrode lead paste formula produced by the company, tested every 50 times during the battery cycle life test according to GB / T22199.1-2017. DETAILED DESCRIPTION
[0029] Example 1
[0030] Lead paste formula for negative electrode of lead-acid battery:
[0031]
[0032] Among them, sulfuric acid solution: density is 1.4±0.001g / cm 3 ;
[0033] Among them, polyester staple fiber, sodium lignin sulfonate, barium sulfate, acetylene black, and sodium polyaspartate are special additives for batteries provided by Guangzhou Edenda;
[0034] Among them, the graphene is Gc-powder 48 produced by Ningbo Moxi Technology Co., Ltd.
[0035] Among them, indium trioxide and vanillin were analytical grade produced by Xilong Scientific Co., Ltd.
[0036] The preparation method of lead paste for negative electrode of lead-acid battery comprises the following steps:
[0037] (1) Add lead powder, lignin, barium sulfate, humic acid, sodium polyaspartate, acetylene black, carboxymethyl cellulose and indium trioxide into a paste mixer and stir for 5 minutes;
[0038] (2) Take 2 parts of the formulated water, add the formulated amount of graphene, fiber, and vanillin, and stir until the vanillin is dissolved, the graphene and fiber are evenly dispersed in the water, and the fiber does not clump.
[0039] (3) Add the remaining amount of deionized water to the paste mixer of step (1) while stirring, and add the suspension produced in step (2) within 3 minutes, and continue wet stirring for 5 minutes;
[0040] (4) Add the formula with a density of 1.4 ± 0.001 g / cm2 into the paste making machine in step (3) while stirring. 3 The sulfuric acid solution is added, and the acid addition time is controlled within 17 minutes. During the acid addition process, when the paste temperature reaches 40°C, the water cooling system is turned on, and when the paste temperature reaches 48°C, the air cooling system is automatically turned on. The maximum temperature of the paste is controlled to be 55°C, and it is stirred evenly.
[0041] (5) When the lead paste temperature is lower than 45°C, it can be taken out of the pot and used for coating the board.
[0042] Example 2
[0043] Lead paste formula for negative electrode of lead-acid battery:
[0044]
[0045] Among them, sulfuric acid solution: density is 1.4±0.001g / cm 3 ;
[0046] Among them, polyester staple fiber, sodium lignin sulfonate, barium sulfate, acetylene black, and sodium polyaspartate are special additives for batteries provided by Guangzhou Edenda;
[0047] Among them, the graphene is Gc-powder 48 produced by Ningbo Moxi Technology Co., Ltd.
[0048] Among them, indium trioxide and vanillin were analytical grade produced by Xilong Scientific Co., Ltd.
[0049] The preparation method of lead paste for negative electrode of lead-acid battery comprises the following steps:
[0050] (1) Add lead powder, lignin, barium sulfate, humic acid, sodium polyaspartate, acetylene black, carboxymethyl cellulose and indium trioxide into a paste mixer and stir for 5 minutes;
[0051] (2) Take 2 parts of the formulated water, add the formulated amount of graphene, fiber, and vanillin, and stir until the vanillin is dissolved, the graphene and fiber are evenly dispersed in the water, and the fiber does not clump.
[0052] (3) Add the remaining amount of deionized water to the paste mixer of step (1) while stirring, and add the suspension produced in step (2) within 3 minutes, and continue wet stirring for 5 minutes;
[0053] (4) Add the formula with a density of 1.4 ± 0.001 g / cm2 into the paste making machine in step (3) while stirring. 3 The sulfuric acid solution is added, and the acid addition time is controlled within 17 minutes. During the acid addition process, when the paste temperature reaches 40°C, the water cooling system is turned on, and when the paste temperature reaches 48°C, the air cooling system is automatically turned on. The maximum temperature of the paste is controlled to be 55°C, and it is stirred evenly.
[0054] (5) When the lead paste temperature is lower than 45°C, it can be taken out of the pot and used for coating the board.
[0055] Example 3
[0056] Lead paste formula for negative electrode of lead-acid battery:
[0057]
[0058] Among them, sulfuric acid solution: density is 1.4±0.001g / cm 3 ;
[0059] Among them, polyester staple fiber, sodium lignin sulfonate, barium sulfate, acetylene black, and sodium polyaspartate are special additives for batteries provided by Guangzhou Edenda;
[0060] Among them, the graphene is Gc-powder 48 produced by Ningbo Moxi Technology Co., Ltd.
[0061] Among them, indium trioxide and vanillin were analytical grade produced by Xilong Scientific Co., Ltd.
[0062] The preparation method of lead paste for negative electrode of lead-acid battery comprises the following steps:
[0063] (1) Add lead powder, lignin, barium sulfate, humic acid, sodium polyaspartate, acetylene black, carboxymethyl cellulose and indium trioxide into a paste mixer and stir for 5 minutes;
[0064] (2) Take 2 parts of the formulated water, add the formulated amount of graphene, fiber, and vanillin, and stir until the vanillin is dissolved, the graphene and fiber are evenly dispersed in the water, and the fiber does not clump.
[0065] (3) Add the remaining amount of deionized water to the paste mixer of step (1) while stirring, and add the suspension produced in step (2) within 3 minutes, and continue wet stirring for 5 minutes;
[0066] (4) Add the formula with a density of 1.4 ± 0.001 g / cm2 into the paste making machine in step (3) while stirring.3 The sulfuric acid solution is added, and the acid addition time is controlled within 17 minutes. During the acid addition process, when the paste temperature reaches 40°C, the water cooling system is turned on, and when the paste temperature reaches 48°C, the air cooling system is automatically turned on. The maximum temperature of the paste is controlled to be 55°C, and it is stirred evenly.
[0067] (5) When the lead paste temperature is lower than 45°C, it can be taken out of the pot and used for coating the board.
[0068] Comparative Example 1
[0069] Negative lead paste formula without sodium polyaspartate:
[0070]
[0071] Among them, sulfuric acid solution: density is 1.4±0.001g / cm 3 ;
[0072] The purchase sources of the corresponding materials in the lead paste additive and the lead paste preparation method are the same as those in Example 1.
[0073] Comparative Example 2
[0074] Negative lead paste formula without adding carboxymethyl cellulose:
[0075]
[0076] Among them, sulfuric acid solution: density is 1.4±0.001g / cm 3 ;
[0077] The purchase sources of the corresponding materials in the lead paste additive and the lead paste preparation method are the same as those in Example 1.
[0078] Comparative Example 3
[0079] Negative lead paste formula without adding indium trioxide and vanillin:
[0080]
[0081] Among them, sulfuric acid solution: density is 1.4±0.001g / cm 3 ;
[0082] The purchase sources of the corresponding materials in the lead paste additive and the lead paste preparation method are the same as those in Example 1.
[0083] Test Example 1
[0084] Positive plate lead paste formula and preparation process:
[0085]
[0086]
[0087] Among them, sulfuric acid solution: density is 1.4±0.001g / cm 3 ;
[0088] Among them, polyester staple fibers, graphene, stannous sulfate, antimony trioxide, and bismuth trioxide are special additives for batteries provided by Guangzhou Edenda;
[0089] The preparation method of lead-acid battery positive electrode lead paste comprises the following steps:
[0090] (1) Add lead powder, stannous sulfate, bismuth trioxide and antimony trioxide into a paste mixer and stir for 5 minutes;
[0091] (2) Take 2 parts of water from the formula water, add the formula amount of graphene and polyester staple fibers into it, and stir until the graphene and fibers are evenly dispersed in the water and there is no clumping of the fibers.
[0092] (3) Add the remaining amount of deionized water to the paste mixer of step (1) while stirring, and add the suspension produced in step (2) within 3 minutes, and continue wet stirring for 5 minutes;
[0093] (4) Add the formula with a density of 1.4 ± 0.001 g / cm2 into the paste making machine in step (3) while stirring. 3 The sulfuric acid solution is added, and the acid addition time is controlled within 12 minutes. During the acid addition process, when the paste temperature reaches 68°C, the water cooling system is turned on, and when the paste temperature reaches 72°C, the air cooling system is automatically turned on. The maximum temperature of the paste is controlled to be 80°C, and it is stirred evenly;
[0094] (5) When the lead paste temperature is lower than 45°C, it can be taken out of the pot and used for coating the board.
[0095] The lead pastes in Examples 1 to 3 and Comparative Examples 1 to 2 were respectively made into negative plates, which were combined with positive plates made according to the positive plate lead paste formula and preparation process to prepare 20AH batteries of the same model, and the battery performance was tested.
[0096] (1) 2Hr capacity test
[0097] Figure 1 This is a comparison chart of the 2Hr capacity of 20AH batteries made of Examples 1 to 3 and Comparative Examples 1 to 3 and paste tested according to GB / T22199.1-2017.
[0098] It can be seen from the test results that all embodiments and comparative examples exceed the capacity test standard ≥20AH of GB / T22199.1-2017, among which for Embodiment 2 and Comparative Example 2, the 2Hr capacity is relatively the highest, exceeding the standard by 12.5%, which shows that the process improves the battery capacity.
[0099] (2) -18℃ low temperature capacity test
[0100] Figure 2 This is a comparison chart of the -18°C low-temperature capacity of 20AH batteries made of Examples 1 to 3 and Comparative Examples 1 to 3 and pastes tested according to GB / T22199.1-2017.
[0101] It can be seen from the test results that all embodiments and comparative examples exceed the 18°C low-temperature capacity test standard ≥14AH of GB / T22199.1-2017, but the low-temperature capacity of comparative example 2 is obviously lower than that of the other embodiments and comparative examples, which shows that sodium polyaspartate has a better effect.
[0102] (3) Capacity retention rate test
[0103] Figure 3 This is a comparison chart of the capacity retention rates of 20AH batteries made of Examples 1 to 3 and Comparative Examples 1 to 3 and pastes tested according to GB / T22199.1-2017.
[0104] From the test results, it can be seen that, except for Comparative Example 3 which did not reach the capacity retention rate standard of GB / T22199.1-2017, all the other embodiments and comparative examples exceeded the standard by ≥90%, and Comparative Example 3 was significantly lower than the other embodiments and comparative examples, which shows that indium trioxide and vanillin have the effect of preventing self-discharge.
[0105] (4) Battery life reliability test
[0106] Figure 4 This is a comparison chart of battery cycle life of 20AH batteries made of Examples 1 to 3 and Comparative Examples 1 to 3 and paste tested according to GB / T22199.1-2017.
[0107] From the test results, all the batteries of the embodiments and comparative examples exceed the standard of life reliability ≥ 200 times of GB / T22199.1-2017, which shows that the formula and unique preparation process have the characteristics of extending the life of the battery. However, the life of comparative example 3 is the shortest among the embodiments and comparative examples, which may be due to the absence of indium trioxide and vanillin to inhibit the loss of water in the later stage.
[0108] (5) -18℃ low temperature capacity test during cycle life test
[0109] Figure 5 This is a comparison chart of the low-temperature capacity of 20AH batteries made of Examples 1 to 3 and Comparative Examples 1 to 3 and pastes during the life reliability test according to GB / T22199.1-2017. After being fully charged, they are kept in a low-temperature box at a constant temperature of -18°C for 5 hours every 49 times, and then discharged at 10A to 10.5V / battery.
[0110] From the test results, Example 1, Example 2, and Example 3 all achieved good low-temperature effects in the "-18°C low-temperature capacity test during cycle life test", and Comparative Example 2 and Comparative Example 1 were significantly better than the battery of Comparative Example 1.
Claims
1. A lead paste for negative electrode of a lead-acid battery, comprising lead powder, a negative electrode additive, deionized water and a synthetic acid, characterized in that: Based on 100 parts by weight of lead powder, the negative electrode additive includes the following components in parts by weight:
2. The negative electrode lead paste for lead-acid battery according to claim 1, characterized in that: Based on 100 parts by weight of lead powder, the negative electrode additive includes the following components in parts by weight:
3. The negative electrode lead paste for lead-acid battery according to claim 1, characterized in that: The adding ratio of humic acid, sodium polyaspartate and lignin is 2-3:1:1-1.
5.
4. The negative electrode lead paste for lead-acid battery according to claim 1, characterized in that: The addition ratio of the graphene to acetylene black is 1:2-2.
33.
5. The negative electrode lead paste for lead-acid battery according to claim 1, characterized in that: Based on 100 parts by weight of the lead powder, the weight of the deionized water is 10.5 to 11 parts.
6. The negative electrode lead paste for lead-acid battery according to claim 1, characterized in that: Based on 100 parts by weight of the lead powder, the weight of the composite acid is 7.6 to 8 parts.
7. The negative electrode lead paste for lead-acid battery according to claim 6, characterized in that: The density of the composite acid is 1.4±0.001 g / cm 3 .
8. The method for preparing the negative electrode lead paste for lead-acid batteries according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Add lead powder, lignin, barium sulfate, humic acid, sodium polyaspartate, acetylene black, carboxymethyl cellulose and indium trioxide into a paste mixer and stir evenly; (2) Take 2 parts of water from the formula water, add the formula amount of graphene, fiber, and vanillin, and stir until the vanillin is dissolved, the graphene and fiber are evenly dispersed in the water, and the fiber does not clump; (3) adding deionized water into the paste mixer while stirring, and adding the suspension produced in step (2) while stirring evenly; (3) Adding the paste acid into the paste mixing machine while stirring, controlling the paste temperature to a maximum of 40 to 55° C., and stirring evenly; (4) When the lead paste temperature is lower than 45°C, it can be taken out of the pot and used for coating the board.
Citation Information
Patent Citations
A novel graphene anode active compound used for lead-acid storage batteries and a preparing method thereof
CN104900876A
Negative electrode lead paste of lead storage battery, negative electrode plate and lead storage battery
CN113394400A
Lead-acid cell cathode lead-paste modified by grapheme dispersion liquid, and preparation method thereof
CN103367753A
Negative electrode lead paste and negative electrode plate of lead storage battery used at low temperature
CN112786843A